Neurosonological Examination: A Non-Invasive Approach for the Detection of Cerebrovascular Impairment in AD - Urbanova, Barbora; Tomek, Ales; Mikulik, Robert; Magerova, Hana; Horinek, Daniel; Hort, Jakub (Frontiers in Behavioral Neuroscience, 2014)
There has been a growing interest in vascular impairment associated with Alzheimer’s disease (AD). This interest was stimulated by the findings of higher incidence of vascular risk factors in AD. Signs of vascular impairment were investigated notably in the field of imaging methods. Our aim was to explore ultrasonographic studies of extra- and intracranial vessels in patients with AD and mild cognitive impairment (MCI) and define implications for diagnosis, treatment and prevention of the disease. The most frequently studied parameters with extracranial ultrasound are intima-media thickness in common carotid artery, carotid atherosclerosis, and total cerebral blood flow. The transcranial ultrasound concentrates mostly on flow velocities, pulsatility indices, cerebrovascular reserve capacity, cerebral microembolization. Studies suggest there is morphological and functional impairment of cerebral circulation in AD compared to healthy subjects. Ultrasound as a non-invasive method could be potentially useful in identifying individuals in a higher risk of progression of cognitive decline.